Prevalence of Tobacco Smoking and Factors Associated with the Initiation of Smoking among University Students in Dhaka, Bangladesh - Sahadat Hossain; Shakhaoat Hossain; Fahad Ahmed; Rabiul Islam; Tajuddin Sikder; Abdur Rahman (University Library System, University of Pittsburgh, 2017)
Introuduction: Tobacco smoking is considered to be the key preventable risk factor for morbidity and mortality at the global level. The aim of this study was to determine the prevalence of tobacco smoking and factors associated with the initiation of smoking among university students in Dhaka, Bangladesh. Methods: A cross-sectional survey study was conducted with 264 students of Jahangirnagar University, Dhaka, Bangladesh in 2015. A standard, self-administered questionnaire consisting of questions on socio-demographic variables, tobacco smoking status, family and peer tobacco smoking history, attitudes and beliefs about tobacco smoking, as well as knowledge about the negative health consequences of tobacco smoking was administered to participants. Data were analyzed using logistic regression models, chi square, and Fisher exact tests. Results: The overall prevalence of tobacco smoking was 60.2%, where males smoked at higher rates than females (68.81% and 19.56%, respectively). The influence of friends was the most significant reason for initiating tobacco smoking (OR: 0.862; CI: 0.810-0.917). Perception regarding tobacco smoking was significantly related to continuing tobacco use. Logistic regression models identified that smoking-related attitudes, potential health problems, and family members dying from cardiovascular disease and cancer were significantly associated with tobacco smoking. Conclusion: The current tobacco smoking prevalence among university students in Bangladesh is over 60%. We suggest adopting WHO Framework Convention on Tobacco Control (FCTC) policies, especially for university students.